DETERMINATION OF THE MAIN INDICATORS OF THE ENGINE COOLING SYSTEM - Sh. I. Tojiboyev (European Science Publishing, 2023)
The engine cooling system plays a very important role in ensuring the main operational properties of agricultural machines, and the reliability of the machines largely depends on the ability of the engine to work continuously. During the design of agricultural machines, the choice of the engine cooling system is the initial and initial process, that is, the ability to choose the type of cooling system actually goes back to the choice of the main indicators of the engine cooling system.
Keywords: Cooling system, cooling surface area, air flow consumption.